How do you simplify #(7y -x)^2#?

3 Answers
Jan 25, 2017

Answer:

#49y^2 + x^2 - 14xy #

Explanation:

It is a binomial squared:

# (a + b)^2 = a^2 + b^2 + 2ab#

Jan 25, 2017

Answer:

See below.

Explanation:

This is a binomial so we can make use of the standard formula

#(color(red)"a"-color(blue)"b")^2# #=# #color(red)"a"^2# - #2color(red)"a"color(blue)"b"# + #color(blue)"b"^2#

For our purposes, #color(red)("a"=7y# and #color(blue)("b"=x# . Putting the values in the above given equation we obtain:

#(7y -x)^2# = #49y^2 -2*7y*x + x^2#

#=># #(7y -x)^2# = #49y^2 -14xy + x^2#

Jan 25, 2017

Answer:

#49y^2-14yx+x^2#

Explanation:

#(7y-x)^2#

#color(white)(aaaaaaaaaaaaa)##7y-x#

#color(white)(aaaaaaaaaaaaa)##7y-x#

#color(white)(aaaaaaaaaaa)##---#

#color(white)(aaaaaaaaaaaaa)##49y^2-7yx#

#color(white)(aaaaaaaaaaaaaaaaa)##-7yx+x^2#

#color(white)(aaaaaaaaaaaaa)##------#

#color(white)(aaaaaaaaaaaa)##49y^2-14yx+x^2#